“Blame it on the Comorbidities”: A 5-Year Follow-Up of 53 Chronic Dialysis-Dependent Patients Who Underwent Cardiac Surgery - Deutsch, Oliver; Rippinger, Nathalie; Spiliopoulos, Kyriakos; Eichinger, Walter; Gansera, Brigitte (The Thoracic and Cardiovascular Surgeon, 2016)
Objectives This study evaluates midterm survival rates and risk factors for mortality of chronic dialysis-dependent patients undergoing cardiac surgery.Methods Fifty-three dialysis-dependent patients (34 males, aged 67 ± 12 years) with end-stage renal disease operated within March 2007 and May 2012 were analyzed retrospectively. Survival rates were calculated using Kaplan–Meier methods. Predictors of midterm survival were identified with multivariate Cox-regression analysis.Results Twenty-three patients received isolated coronary artery bypass graft surgery, 17 received isolated valve replacement, and 13 received combined procedures. Thirty-day mortality was 24.5% (n = 13). Follow-up was complete for 94.3% (n = 50). Survival rates at 1, 3, and 5 years were: 82, 50, and 17%, respectively. Neither age, gender, poor ejection fraction, emergency, ECC/X-clamp (cross-clamp) time, nor use of left internal thoracic artery or right internal thoracic artery had any influence on midterm survival. Causes of death within midterm follow-up period were related to cardiac events in 16% and neurological events in 16%. In the majority (47%), cause of death was associated with peripheral arterial disease (PAD).The only comorbidity, which could be identified as a significant risk factor, was PAD (p = 0.035). Five patients underwent successful renal transplantation within the follow-up period.Conclusion Although 30-day mortality in this high-risk patient population was increased, midterm survival rates were comparable to the results described in the literature. Cause of death within midterm follow-up period was mostly noncardiac related. Given the limited number of patients, predictors for enhanced 30-day mortality, such as preoperative myocardial infarction, prolonged extracorporeal circulation, operation time, and diabetes mellitus, did not have an influence on midterm survival.
Keywords: cardiac; kidney; peripheral vascular disease